2014
DOI: 10.1155/2014/184278
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Therapeutic Benefit on Lactoferrin in Patients with Colorectal Cancer Receiving Chemotherapy

Abstract: A double-blinded parallel randomized controlled clinical trial was conducted on two groups of colorectal cancer patients to study the therapeutic benefit of orally administered bovine lactoferrin (bLF) on colorectal cancer patients having age ranges from 20 to 71 years and who received 5-fluorouracil and leucovorin calcium. Test group (15 patients) received oral bLF 250 mg/day beside chemotherapy for three months. Control group (15 patients) received chemotherapy only. Serum lactoferrin (LF), serum glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Studies of other mammals such as pigs and rats have indicated the positive role of orally administrated LF on liver functions (Burrin, Wang, Heath, & Dudley, ; Tsubota et al., ). Recently, dietary LF has been shown to improve liver and kidney functions in humans (Moastafa et al., ). This is because dietary LF may protect liver against damages by reactive oxygen species (ROS) as LF can serve as an antioxidant (Actor et al., ; Legrand, Elass, Carpentier, & Mazurier, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of other mammals such as pigs and rats have indicated the positive role of orally administrated LF on liver functions (Burrin, Wang, Heath, & Dudley, ; Tsubota et al., ). Recently, dietary LF has been shown to improve liver and kidney functions in humans (Moastafa et al., ). This is because dietary LF may protect liver against damages by reactive oxygen species (ROS) as LF can serve as an antioxidant (Actor et al., ; Legrand, Elass, Carpentier, & Mazurier, ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum lysozyme is also secreted by tissue macrophages (Alhazmi, Stevenson, Amartey, & Qin, ). LF is known to induce changes in the leucocytes of the innate immune system through increasing natural killer cell activity, promoting the function of neutrophils by enhancing phagocytic activity and activating macrophages through increasing cytokine but limiting intracellular pathogen proliferation (Moastafa et al., ). Based on the results of this study and the findings of previous studies indicating the positive role of dietary LF on non‐specific immune status in different aquatic species such as the Asian catfish (Kumari, Swain, & Sahoo, ), rainbow trout (Rahimnejad et al., ; Sakai et al., ) and Siberian sturgeon (Eslamloo et al., ), it may be claimed that fish immune cells are probably activated by dietary LF and/or its bioactive fragments.…”
Section: Discussionmentioning
confidence: 99%
“…The effects seen with bovine LF supplementation were not significantly different from the control, with the exception ofan increased anti-inflammatory and immunomodulatory effect. In addition, several side-effects (liver and kidney toxicity and mucositis) associated with the chemotherapy were alleviated in the bovine LF treated group and certain symptoms such as anemia were decreased [87].…”
Section: Anticancer Effects Of Milk Proteins In Humansmentioning
confidence: 90%
“…The mechanisms of action are not yet understood, but they may involve immunomodulatory effects, an increase in human plasma LF concentration (causing a reduced infiltration of polymorphonuclear leukocytes in the polyps) and possibly the iron chelating activities of LF at the polyp sites [67]. A second study was recently conducted with colorectal cancer patients undergoing chemotherapy who were supplemented with 250 mg/day bovine LF for 3 months [87]. The effects seen with bovine LF supplementation were not significantly different from the control, with the exception ofan increased anti-inflammatory and immunomodulatory effect.…”
Section: Anticancer Effects Of Milk Proteins In Humansmentioning
confidence: 99%
“…At this point, we don't have any explanation as to why platelet counts are lower in LFKO -/-diabetic mice when compared to WT diabetic mice. However, there are reports, which show that oral administration of LF increased the platelet counts [52]. Furthermore, exogenous LF add-back to LFKO -/-mice studies are needed to elucidate the role of LF on platelet counts in diabetes.…”
Section: Page -05mentioning
confidence: 99%